Rotation stability of a toric intraocular lens with a second capsular tension ring - Sagiv, Oded; Sachs, Dan (Journal of cataract and refractive surgery, 2015)
An Acrysof toric intraocular lens (IOL) and a capsular tension ring (CTR) were implanted in the highly myopic eye of a 74-year-old white man during cataract surgery. On the first postoperative day, the IOL was found 90 degrees from the required position, with a consequent high amount of astigmatism. A second procedure was performed and because it was not possible to secure the toric IOL in the correct position, an additional in-the-bag CTR was inserted, with an immediate optimal outcome. The IOL remained stable up to the final follow-up examination. Co-implantation of a toric IOL and a single CTR has been reported. In our case, 2 CTRs were required to fixate the toric IOL in the correct position. This procedure is simple and safe and should be considered in cases of postoperatively misaligned toric IOLs.